SONIC VELOCITY AND GRAIN CONTACT PROPERTIES IN RESERVOIR SANDSTONES - Storvoll V.; Bjørlykke K. (My University, 2004)
The purpose of this study was to examine the effect of grain contacts and quartz cementation with regard to acoustic wave propagation in sandstones. Grain contacts have been considered essential when relating acoustic velocities to physical rock properties, and a parameter numerically representing the contact area between individual grains (contact length) has been measured. The method used involves digital petrographic microscopy pictures analysed by image analysis software. Other parameters, such as grain size, number of grain-to-grain contacts, cracks, clay content and porosity, have also been closely examined. The results showed that the contact area between sand grains may be useful for explaining velocity variations during the initial stages of quartz cementation and grain framework stiffening. Continued increase in grain-contact area by chemical compaction will have less influence on the sonic velocity compared to variations in porosity. The Garn Fm. from the Norne Field (2.6–2.7 km burial depth), which is in the early phase of initial grain framework stiffening by quartz cementation, and the Garn Fm. from the Kristin Field (4.6–4.7 km burial depth), which is thoroughly quartz cemented, were chosen as sample materials. Log-derived velocities, in addition to some laboratory ultrasonic velocity measurements, were used in this study.
Keywords: sandstones; cementation; contact area; elasticity; sonic velocity